Equity dimensions in initiatives promoting urban health and wellbeing in east and southern Africa - Loewenson, Rene; Mhlanga, Gibson; Gotto, Danny; Chayikosa, Sam; Goma, Fastone; Walyaro, Constance (Frontiers in Public Health, 2023)
Urbanisation in east and southern Africa (ESA) has brought opportunity and wealth together with multiple dimensions of deprivation. Less well documented in published literature on the ESA region are features of urban practice that promote health equity. This work thus aimed to explore features of urban initiatives aimed at improving health and wellbeing in ESA countries and their contribution to different dimensions of health equity. A thematic analysis was implemented on evidence gathered from 52 documents from online searches and ten case studies from Harare, Kampala, Lusaka and Nairobi. Most of the initiatives found focused on social determinants affecting low income communities, particularly water, sanitation, waste management, food security and working and environmental conditions, arising from longstanding urban inequalities and from recent climate and economic challenges. The interventions contributed to changes in social and material conditions and system outcomes. Fewer reported on health status, nutrition and distributional outcomes. The interventions reported facing contextual, socio-political, institutional and resource challenges. Various enablers contributed to positive outcomes and helped to address challenges. They included investments in leadership and collective organisation; bringing multiple forms of evidence to planning, including from participatory assessment; building co-design and collaboration across multiple sectors, actors and disciplines; and having credible brokers and processes to catalyse and sustain change. Various forms of mapping and participatory assessment exposed often undocumented shortfalls in conditions affecting health, raising attention to related rights and duties to promote recognitional equity. Investment in social participation, organisation and capacities across the initiatives showed participatory equity to be a consistent feature of promising practice, with both participatory and recognitional equity acting as levers for other dimensions of equity. There was less evidence of distributional, structural and intergenerational equity. However, a focus on low income communities, links made between social, economic and ecological benefit, and investment in women and young people and in urban biodiversity indicated a potential for gains in these areas. The paper discusses learning on local process and design features to strengthen to promote these different dimensions of equity, and issues to address beyond the local level to support such equity-oriented urban initiatives.